2019
DOI: 10.1186/s42501-019-0029-3
|View full text |Cite
|
Sign up to set email alerts
|

The floristic relationship between the upland and lowland Carboniferous wetlands of Variscan Euramerica — Evidence from some medullosalean pteridosperm fronds

Abstract: Alethopteris grandinii represents remains of fronds of a medullosalean pteridosperm (probably a small tree) that rapidly migrated across the lowland wetland habitats of Variscan Euramerica in middle Asturian (late Moscovian) times. This was probably caused by changing drainage patterns within the lowland coal swamps, in response to climate and landscape changes. However, these medullosaleans had first appeared rather earlier, in early Bolsovian (early Moscovian) times, in upland wetland habitats. These upland … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 38 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…These differences potentially have wider implications as it has been suggested that plant migration from the intramontane basins may have been a significant factor in the vegetation changes observed in the paralic basins (e.g. Thomas 1997, Cleal et al 2009, Thomas & Cleal 2017, Šimůnek & Cleal 2018, Cleal & Cascales-Miñana 2019. Evidently, the ecological factors that drove these temporal and palaeofloristic differences among the medullosaleans at this time will require further work.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…These differences potentially have wider implications as it has been suggested that plant migration from the intramontane basins may have been a significant factor in the vegetation changes observed in the paralic basins (e.g. Thomas 1997, Cleal et al 2009, Thomas & Cleal 2017, Šimůnek & Cleal 2018, Cleal & Cascales-Miñana 2019. Evidently, the ecological factors that drove these temporal and palaeofloristic differences among the medullosaleans at this time will require further work.…”
Section: Discussionmentioning
confidence: 94%
“…However, there are also examples of taxa that seem to have originated in the intramontane basins and only later extended their ranges into the lowland paralic areas. For instance, Cleal & Cascales-Miñana (2019) suggested that alethopterids similar to Alethopteris grandinii (Brongniart) Göppert appeared significantly earlier (early Bolsovian) in the intramontane Saar-Lorraine Basin, and only later (middle Asturian) migrated into the lowland paralic areas when there were landscape changes resulting from the Variscan Orogeny. Although A. grandinii has not been reported from the CWBB, there are fragmentary remains of other alethopterids in the Radnice Member that are normally associated with late Asturian and younger floras in the paralic basins: Alethopteris pseudograndinioides and Alethopteris serlii (e.g.…”
Section: Nýřany Membermentioning
confidence: 99%
“…They are the foliage of a taxonomically coherent ("natural") group of plants but within which at least seven distinct fossil-species can be recognised, each with its own geographical and stratigraphical range. The group of plants originated in the upland intramontane coal swamps of the Variscan Mountains during Duckmantian times and then during the Bolsovian invaded lowland paralic areas of the Variscan Foreland, as part of a major reconfiguration of the coal swamp vegetation also seen with the medullosalean pteridosperms and herbaceous lycopsids (Thomas, 1997;Falcon-Lang, 2004;Thomas & Cleal, 2017;Cleal & Cascales-Miñana, 2019;Šimůnek & Cleal, 2020). This was part of a major reconfiguration of the coal swamp biotas known as the Morganian-Ammanian transition in the middle Bolsovian (e.g., Trueman, 1946) and coincided with global climatic cooling (the onset of the Late Palaeozoic Ice Age Glaciation Phase C4- Fielding et al, 2008Fielding et al, , 2023 causing a drop in sea levels and so less-frequent marine flooding of the paralic basins, and enhanced substrate drainage as the Central Pangaean Mountains expanded northwards (e.g., Jones, 1991Jones, , 1989Gayer et al, 1993).…”
Section: Discussionmentioning
confidence: 99%